IMPLEMENTASI E-SERVICES DALAM PELAYANAN PUBLIK UNTUK MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS (Studi Pada Mal Pelayanan Publik Kota Probolinggo) - Sucahyo, Imam; Yunus, Eko Yudianto; Ifana, Anila (CERED Indonesia, 2025)
This study aims to analyze the implementation of e-services in public service delivery at the Public Service Mall (MPP) of Probolinggo City, in order to enhance transparency and accountability. The background of this research is based on the demands of bureaucratic reform, which encourage digital transformation in public services to create an open and accountable system of governance. This study employs a descriptive qualitative approach, using the e-service implementation theory based on the Information System Success Model by DeLone and McLean (2003), which includes dimensions of system quality, information quality, service quality, system use, user satisfaction, and net benefits. Data were collected through in-depth interviews, observation, and documentation. The findings indicate that the implementation of e-services at MPP Probolinggo has made a positive contribution to improving information access and service efficiency, thereby fostering transparency and accountability in public service delivery. Nevertheless, several challenges were identified, such as limited digital literacy among the public and the need to improve the stability of the electronic service system. This study recommends strengthening human resource capacity, continuous public outreach, and regular evaluations of the e-service system to optimally achieve transparent and accountable public services. Keywords : E-services Public Service, Transparency, Accountability, Public Service Mall